Tournament recovery profiles and physical demands in a collegiate women`s tennis team - Tendero-Ortiz, E.; Johnson, M. J.; Horsfall, C. M.; Vondrasek, J. D.; Grosicki, G. J.; Riemann, B. L.; Flatt, A. A. (The Journal of Strength and Conditioning Research, 2024)
We aimed to characterize recovery profiles and tournament physical demands in women's collegiate tennis players. A Division 1 team (n = 9) participated in the study. Markers of cardiac autonomic (resting heart rate [HR], HR variability), neuromuscular (isometric handgrip strength, seated single-arm shot-put test [SSAPT], hexagon agility, countermovement jump characteristics), and perceptual recovery were obtained before the tournament (baseline) and again 1 and 2 days posttournament. Cardiorespiratory (HR) and movement characteristics from matches were quantified with wearable devices. p values < 0.05 were statistically significant. No recovery markers differed from baseline (p > 0.05), although small effect size reductions 1 day posttournament were noted for SSAPT, hexagon agility, and select countermovement jump characteristics. In addition, hexagon agility times and SSAPT were slower (p < 0.01) and shorter (p < 0.05), respectively, at 1 versus 2 days posttournament. Similarly, relative to 1 day posttournament, perceptual makers were improved 2 days posttournament (ps < 0.05). Mean and peak HR were higher for singles versus doubles matches (p < 0.05). Except for average speed, movement parameters were greater during singles versus doubles matches (p < 0.05). Markers of recovery were minimally affected 1 day posttournament relative to baseline, but perceptual and select neuromuscular markers were most improved 2 days posttournament. Thus, passive rest or limited intensity training 1 day posttournament seems advisable. Competition HR and movement profiles inform practitioners of the cardiorespiratory and locomotor demands of women's collegiate tennis, which may be useful in designing preparatory conditioning programs to ensure that players attain match-specific physical capacities in training before competition.